Ethnobotany Study of Corn (Zea mays. L) in Tamberu Village West Sokobanah Subdistrict Sampang Madura District - Kamiliatul Mufidah; Ari Hayati; Hasan Zayadi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
Corn, which is a tropical grass that is very adaptive to climate change and corn, also has a life span of 75-150 days. Corn can usually grow to reach a height of 3 meters. Corn which usually has a scientific name Zea mays is not like other grain plants, Corn and commonly called jhegung in the language of Madura is a plant that has often been made into cultivated plants and has often been used by the community groups of West Tamberu Village as food as fuel or as animal feed. This study aims to determine the public perception of the benefits of corn plants found in Tamberu Barat Village, Sokobanah District, Sampang Madura Regency. In this study, researchers used descriptive exploratory methods which included: first-hand study, direct observation in the field, interviews using questionnaire guidance, data analysis and documentation of utilization of corn plants. The characteristics of the varieties found in Tamberu Barat Village consist of three varieties, namely local maize plants, hybrid maize plants, sweet corn plants. Public perceptions of corn plants in the western tamberu village are very high potential of corn plants which are used as food (59%), as fuel (10%), as animal feed (13%) and economic needs (18%).